2023
DOI: 10.3390/biology12050735
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Magnesium Status in COVID-19

Abstract: A large amount of published research points to the interesting concept (hypothesis) that magnesium (Mg) status may have relevance for the outcome of COVID-19 and that Mg could be protective during the COVID disease course. As an essential element, Mg plays basic biochemical, cellular, and physiological roles required for cardiovascular, immunological, respiratory, and neurological functions. Both low serum and dietary Mg have been associated with the severity of COVID-19 outcomes, including mortality; both are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 275 publications
0
9
0
Order By: Relevance
“…Magnesium deficiency is associated with depressed immune responses, macrophage inflammatory responses, chronic low-grade inflammation, increased inflammatory responses during viral infections, and an increased risk for an inflammatory cytokine storm. The studies [77,78] demonstrated that the prevalence of hypomagnesemia was higher in patients with COVID-19 compared to healthy individuals. In SARS-CoV-2 infection, serum magnesium level conditions the clinical outcome [79][80][81][82], severity of the disease, disease progression, and mortality [77,78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium deficiency is associated with depressed immune responses, macrophage inflammatory responses, chronic low-grade inflammation, increased inflammatory responses during viral infections, and an increased risk for an inflammatory cytokine storm. The studies [77,78] demonstrated that the prevalence of hypomagnesemia was higher in patients with COVID-19 compared to healthy individuals. In SARS-CoV-2 infection, serum magnesium level conditions the clinical outcome [79][80][81][82], severity of the disease, disease progression, and mortality [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…The studies [77,78] demonstrated that the prevalence of hypomagnesemia was higher in patients with COVID-19 compared to healthy individuals. In SARS-CoV-2 infection, serum magnesium level conditions the clinical outcome [79][80][81][82], severity of the disease, disease progression, and mortality [77,78]. Results of different studies are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Guerrero-Romero et al’s [ 27 ] study underscores the importance of serum magnesium in infectious diseases. It provides a valuable reference point for discussing our findings on serum magnesium levels in TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus (COVID-19) pandemic, which is caused by SARS-CoV-2 infection, has brought a heavy burden to our economic and healthcare systems ( 73 ). As a result, great efforts have been made to better understand its pathogenesis and to implement low-cost prophylactic interventions.…”
Section: Magnesium and Diseases Causing Cardiac Arrestmentioning
confidence: 99%